2021
DOI: 10.33394/jk.v7i4.4414
|View full text |Cite
|
Sign up to set email alerts
|

Learning Facilities that Can Develop Science Process Skills in Indonesia : Review of Experimental Studies

Abstract: Aims of this study are to analyze: (1) types of learning facilities, (2) variants of each type of learning facilities, and (3) recommendations for implementation of variants of types of learning facilities that are empirically proven to be effective in developing the science process skills of students in Indonesia. This research is a literature review study. The data sources are articles in journals and proceedings published from 2016 to 20120. The articles that have been collected are then analyzed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Samosir (2022), on the other hand, found that the Process-Oriented Inquiry learning model had an effect on students' understanding of science concepts and their scientific process skills. Syazali et al (2021), on the other hand, found 7 variables as a result of his study on the learning environment variables that affect the Science Process Skills of Indonesian students. These variables are guided inquiry learning models, inquiry, PBL, PjBL and learning cycles, as well as learning media variables and modules and worksheets.…”
Section: Discussionmentioning
confidence: 99%
“…Samosir (2022), on the other hand, found that the Process-Oriented Inquiry learning model had an effect on students' understanding of science concepts and their scientific process skills. Syazali et al (2021), on the other hand, found 7 variables as a result of his study on the learning environment variables that affect the Science Process Skills of Indonesian students. These variables are guided inquiry learning models, inquiry, PBL, PjBL and learning cycles, as well as learning media variables and modules and worksheets.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a review of the top 10 publications on Science Process Skills research cited as impactful research over the past eleven years, as Table 2 shows. debate skills, ICT, STEM , student-centered teaching, use of a variety of learning tools, hands-on exercises, group activities (Gizaw & Sota, 2023), PhET (Haryadi & Pujiastuti, 2020), mobile scientific investigations (Ekici & Erdem, 2020), guided inquiry, PBL, PjBL, learning cycles, use of learning media, modules and worksheets (Syazali et al, 2021) can train and improve students' science process skills.…”
Section: Figure 3 Overlay Visualization Of Science Process Skills Res...mentioning
confidence: 99%
“…Writing, a form of communication ability, is one of the indicators of SPS [20]. Empirically, learning facilities that can develop these skills include PBL learning models, Inquiry, Guided Inquiry, PjBL, Learning Cycle, and media modules and worksheets [21].…”
Section: Title Editor's Accuracymentioning
confidence: 99%